Institutional Reform and Global Value Chains - Christian Fischer-Thöne; Hartmut Egger (ZBW - Leibniz Information Centre for Economics, 2021)
This paper sets up a model of trade, in which two countries with differing levels of technology specialize on the production of subsets of the global value chain. In the open economy equilibrium, the technologically backward country exports intermediates in exchange for imports of a homogeneous consumption good from the technologically advanced country. This vertical specialization pattern gives the two countries access to different instruments for appropriating rents in the open economy. The technologically advanced country can impose an import tariff on intermediates to lower foreign wages and increase national welfare. An import tariff is ineffective for the technologically backward economy, which can instead lower institutional quality and allow its workers to partially expropriate firms and directly consume intermediate goods at a utility discount. In a non-cooperative policy equilibrium, welfare levels of the two countries will fall to their autarky levels. This gives scope for a trade agreement that conditions tariff reductions on institutional quality improvements and is beneficial for both countries. A beneficial trade agreement may not exist if the import tariff has an upper bound.
Keywords: F12; F13; F68; 330; Global value chains; trade policy; institutional quality; tariffs